Mechanochemically driven formation of protective carbon films from ethanol environment. (December 2022) - Shirani, A.; Li, Y.; Smith, J.; Curry, J.F.; Lu, P.; Wilson, M.; Chandross, M.; Argibay, N.; Berman, D.
Abstract: Wear and degradation of interfaces remain a significant roadblock in commonly used mechanical assemblies across various industries, resulting in loss of their efficiency and ultimately functionality. To advance the state-of-the-art in tribological applications, new materials must be developed not only to resist degradation, wear, and higher frictional losses in extreme environments (i.e. high temperatures, contact/shear forces, etc.), but also to benefit from them. By adopting hard, catalytic interfaces, a wide range of contact conditions can emerge where mechanochemical interactions lead to the formation of protective or self-healing lubricious films. Here, we demonstrate the mechanochemically driven formation of protective carbon films on Pt-Au alloys during sliding in an ethanol environment. We demonstrate the effect of temperature and contact pressure on film formation. The films formed on Pt-Au alloys exhibit a highly graphitic structure as indicated by Raman and Transmission Electron Microscopy (TEM) analyses. The observed results are further supported by molecular dynamics simulations that show the changes in the dissociation and transformation of ethanol molecules with applied pressure and temperature. The results create a new understanding of transformations in the contact and suggest a solution for addressing tribological challenges in the mechanical systems operated in low viscosity fuels. Highlights: Mechanochemically driven formation of protective graphitic carbon films on Pt-Au alloys from ethanol environment is observed. Formation of the film reduces friction and suppresses wear of the sliding surfaces. The rate of the film growth is highly dependent on temperature and contact pressure on film formation. Molecular dynamics simulations indicate that the temperature change has a much stronger effect oon tribocatalysis than the contact pressure.